The problem of determining the sound root and its semantics using the example of one sound of the Kabardino-Circassian language - Musadin L. Kardanov (Кавказология, 2025)
Additional analysis in determining the semantics of sound roots, which in Adyghe studies are considered non-independent root elements, allows us to conclude that in the modern Kabardian-Circassian language, grammaticalized morphemes were once carriers of certain meanings. Based on the identified micro-meanings of sounds that allow us to decipher words, we put forward a hypothesis about the hierarchy of sounds in them, which is confirmed in examples from the language. This is a new approach not only in Adyghe studies but also in linguistics in general for determining the meaning of a word. The cardinal difference between our research and the followers of phonosymbolism is that, denying symbolism in sounds, we find its end-to-end meaning in all words of which it is a component and do not consider this the starting point for sound. We hypothesize that the absolute semantics of sound can only be determined at the intersection of linguistics and natural sciences. Our research establishes a viewpoint for identifying original and borrowed words, because many lexical units lack a reasoned multi-aspect analysis connecting them to a particular language.